Rhetorical Strategies In Prabowo Subianto’s 2024 Presidential Debate: Implications For Language and Civic Education at The Tertiary Level - Sari, Lusi Komala; Apakama, Lusi Mgbemgasha (Mindset : Jurnal Pemikiran Pendidikan dan Pembelajaran, 2025)
In the 2024 Presidential Debate, Prabowo Subianto (PS) attracted public attention not only due to his political profile and electability, but also because of his rhetorical delivery in presenting his national vision and mission. This study analyzes the persuasive power of rhetorical elements in a five-minute speech segment delivered by PS during the vision and mission session. Grounded in Aristotle’s classical rhetorical theory, the research adopts a descriptive qualitative approach supported by critical discourse analysis. The findings reveal that PS employed the three rhetorical appeals: logos, ethos, and pathos, in a balanced and strategic manner. This suggests a mature rhetorical style and an effective adaptation to the communicative demands of electoral democracy. Furthermore, this study contributes to Southeast Asian rhetorical and political discourse studies by highlighting how classical rhetorical strategies remain relevant and impactful in contemporary political communication. In addition, the findings hold pedagogical significance for higher education, particularly in the teaching of language, communication, and civic education. The rhetorical strategies observed in PS’s speech can serve as authentic learning materials for developing students’ rhetorical awareness, critical thinking, and public speaking skills, especially within the framework of democratic engagement and media literacy.